Radiation exposure management techniques during endoscopic retrograde cholangio-pancreatography procedures - Sulieman, A.; Tamam, N.; Khandaker, Mayeen Uddin *; Bradley, D.A. *; Padovani, R. (Elsevier, 2021)
One the most complicated gastrointestinal procedures, endoscopic retrograde cholangio-pancreatography (ERCP) uses fluoroscopy guidance of an endoscope to diagnose and treat hepatobiliary system pathologies. As is true of all approved interventional radiology, it is justified by the massive benefit that it is capable of delivering, one which for the patient far outweighs the risks from radiation exposure. Nevertheless, for both patients and staff there is a need to minimize the risk of carcinogenesis and the potential for tissue reactions. Recent concern has been shown in regard to radiation induced eye lens opacifications and cataract, most particularly for the members of staff who during their regular theatre practice are in closest contact with the patient. Therefore, optimum balance between benefit versus radiation risk is required. This study reviews patient and staff dose during ERCP procedures, also seeking to provide comprehensive data regarding radiation exposure management techniques. Patient and staff doses depend on the operators, equipment and patient related factors, benefitting from awareness and experience in respect of radiation protection techniques and the availability of modern fluoroscopic equipment. It is apparent that in high workload departments, staff doses to eye lens may exceed the limits on annual exposure.